If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 1b + -7 Reorder the terms: 3 = -7 + 1b Solving 3 = -7 + 1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 3 + -1b = -7 + 1b + -1b Combine like terms: 1b + -1b = 0 3 + -1b = -7 + 0 3 + -1b = -7 Add '-3' to each side of the equation. 3 + -3 + -1b = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -1b = -7 + -3 -1b = -7 + -3 Combine like terms: -7 + -3 = -10 -1b = -10 Divide each side by '-1'. b = 10 Simplifying b = 10
| 10x+30=12x+14 | | 10-x+18=7x-4 | | -15(k+15)=-270 | | 40-(40-x)+40-x+x=40 | | x(5-3)+6=3x+(-19+18) | | a-4/5 | | N/6+19=22 | | -3x+4y-12=0 | | 4(k+6)=6(k+2) | | 7+4(-3+8a)=155 | | 2+3x/5+4-x/3=46/15 | | -9(4b+4)+(37b-2)=0 | | 42.95m+60=57.95m | | (X+11)+(x+11)=104 | | 4=9p+50 | | -3x+4y-2=0 | | -(8-x)=x-2(2-x) | | 30x+29=-68 | | -42+r=47 | | 42.95x+60=57.95m | | 5r-(r+2)=3(r-1)+6 | | -5r-6+4r=2 | | X/3-19=-21 | | -12+5=12-19 | | z/6+2=4-z/6 | | 4^2-(-5^2)/45+5 | | 2=v-(-3) | | -1/2x-5=15 | | 2x^2+5=5x^2-27 | | X+11+x+11=104 | | f/m=a | | 8-3(m-4)=2m |